In Situ Accurate Analysis of Colloidal Nanoparticles via Four Wave Mixing. (2nd January 2018) - Wu, Jian; Xiang, Dao; Hsueh, Ching-Chung; Rottler, Jörg; Gordon, Reuven
ABSTRACT: Four-wave mixing (FWM) is used to measure the vibrational modes of nanoparticles in solution. The vibrations give information about the particle size, material properties and shape. This method has been used for in-situ monitoring of the growth of nanoparticles with high accuracy, as confirmed by electron microscopy analysis. We observe a threshold in the FWM signal which we believe is from a cavity forming around the nanoparticles that reduces viscous damping. We have observed this effect in molecular dynamics simulations as well.